Magnetically controlled graphene field-effect transistor biosensor for highly sensitive detection of cardiac troponin I - Zhu, Xiaofeng; Cheng, Kangning; Ding, Yue; Liu, Huanqing; Xie, Shuqi; Cao, Yuwei; Yue, Weiwei (Discover nano, 2023)
Herein, we have constructed a magnetic graphene field-effect transistor biosensor (MGFETs) for highly sensitive detection of cardiac troponin I (CTNI). Graphene films transferred to ITO conductive glass as conductive channels. CTNI aptamer was immobilized onto the graphene film via 1-pyrene-butanoic acid succinimidyl ester (PBASE) to capture CTNI. Magnetic nanobeads (MBs) modified with CTNI antibody were added to the reaction chamber to form an aptamer/CTNI/antibody/magnetic nanobeads sandwich-type complex. We found that the magnetic force exerted on the complex leads to an impedance change of the graphene film. The reason for this result is that the magnetic field exerts an influence on the MBs, causing CTNI aptamer strand to bend, resulting in a change in the distance between the double conductive layers of the graphene film surface and the test solution. With periodic sampling integration, different concentrations of CTNI can be detected with high sensitivity. Due to the stringent recognition capability and high affinity between the CTNI aptamer and CTNI, MGFETs have the potential to detect various types of proteins. Furthermore, MGFETs also have the potential to be utilized for the detection of DNA or specific cells in the future.